1996
DOI: 10.1007/bf02254960
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution fluorescencein situ hybridization ofRBM- andTSPY-related cosmids on released Y chromatin in humans and pygmy chimpanzees

Abstract: Applying two-colour fluorescence in situ hybridization (FISH) we simultaneously hybridized RBM- and TSPY-related cosmids to Y chromosomes in prophase and to released Y chromatin in interphase nuclei of man and pygmy chimpanzee. Whereas, even on prophasic Y chromosomes, no resolution of the overlapping RBM and TSPY signal clusters could be achieved, the RBM and TSPY signals are completely separated from each other in our maximum released Y chromatin stretches in interphase nuclei. These results unequivocally le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…3), it can be concluded that the CDY and DAZ genes have undergone species-specific amplifications and rearrangements within the non-recombining parts of the Y chromosomes of human and great apes. This is in accordance with our comparative FISHmapping results for DAZ, RBMY and TSPY genes on the Y chromosomes of a variety of higher primates (Schempp et al, 1995;Conrad et al, 1996;Gläser et al, 1998b). Such speciesspecific amplifications, and rearrangements of genes within NRY are obviously tolerated as long as no interference with male fertility results.…”
Section: Resultssupporting
confidence: 74%
“…3), it can be concluded that the CDY and DAZ genes have undergone species-specific amplifications and rearrangements within the non-recombining parts of the Y chromosomes of human and great apes. This is in accordance with our comparative FISHmapping results for DAZ, RBMY and TSPY genes on the Y chromosomes of a variety of higher primates (Schempp et al, 1995;Conrad et al, 1996;Gläser et al, 1998b). Such speciesspecific amplifications, and rearrangements of genes within NRY are obviously tolerated as long as no interference with male fertility results.…”
Section: Resultssupporting
confidence: 74%
“…The third event is a paracentric inversion with one breakpoint in PAC 76F02 that installs the contig's actual orientation on the human Y chromosome and splits the Y/1-homologous region in two parts. Comparing this model to FISH patterns produced by DNA probes of multi-copy Y-chromosomal gene families like CDY, DAZ, RBMY and TSPY on human and chimpanzee Y chromosomes (Schempp et al, 1995;Conrad et al, 1996;Gläs-er et al, 1998;Wimmer et al, 2002c), we are able to demonstrate orthology between the euchromatic part of the short arm of the chimpanzee Y chromosomes and the euchromatic human Yq11.22 → q11.23 region, that supports our theoretical model of human Y evolution.…”
Section: Discussionsupporting
confidence: 62%
“…Available cytogenetic data on the evolution of chromosome Y in primates concern the SRY ( Toder et al 1993), YRRM and TSPY genes (Guttenbach et al 1992;Schempp et al 1995;Conrad et al 1996), the Xp22 genes (Meroni et al 1996;Glaser et al 1997a), and the Y-linked genes (Glaser et al 1997b). Most of the probes used in these studies contain expressed sequences, which can be assumed to be under stringent selective pressure.…”
Section: Introductionmentioning
confidence: 98%